The Making of Modern Liberalism - Ryan, Alan, 1940- (Book collections on Project MUSE., 2012)
This book is a deep and wide-ranging exploration of the origins and nature of liberalism from the Enlightenment through its triumphs and setbacks in the twentieth century and beyond. The book is the fruit of more than four decades during which the author reflected on the past of the liberal tradition--and worried about its future. This is essential reading for anyone interested in political theory or the history of liberalism. The book consists of five parts. It covers subjects such as liberalism, freedom, the liberal community and the death penalty, Thomas Hobbes's political philosophy, individualism, human nature, John Locke on freedom, John Stuart Mill's political thought, utilitarianism and bureaucracy, pragmatism, social identity, patriotism, self-criticism, and more.